Mental Health Literacy of Health Workers in Selected Health Facilities of Tanahun District, Nepal - Sumitra Parajuli; Dikshya Wagle; Jiwan Kumar Poudyal; Govinda Prasad Dhungana (Journal of Balkumari College, 2025)
Mental health literacy involves knowledge and belief about mental disorders that support their recognition, management, and prevention. This study aimed to assess the mental health literacy among the health workers of selected health facilities. A descriptive cross-sectional study was conducted using a complete enumerative sampling technique among 141 health workers from the selected 18 health facilities. Data were collected through a self-administered questionnaire utilizing the standardized Mental Health Literacy Scale (MHLS) tool and analyzed using the Statistical Package for Social Sciences (SPSS) version 22, utilizing both descriptive and inferential statistics. Among the 141 participants, half (49.6%) hold a certificate-level qualification, and 63.1% had no formal education in mental health. Additionally, 74.5% had not received any form of in-service training related to mental health. The health workers’ MHL scores ranged from 90 to 144, with an overall mean of 117±10.49(CV=8%), indicating a moderate level of MHL. Among six attributes of MHLS, a greater dispersion was found in Knowledge of risk factors and causes of mental illness (CV=21%) and knowledge of self-treatment (CV=25%). Health workers with less than five years of work experience (P<0.017) and bachelor’s level education (P<0.001) had significantly higher MHLS. There was no significant difference in mean MHLS between male and female participants, with and without formal mental health qualifications, and mental health-related in-service education. MHL of health workers was moderate, and higher academic qualifications improve the knowledge and attitude of health workers. Mental health education should be integrated into all levels of the medical curriculum, and strengthened in-service training is essential to enhance the competency of health workers.